Microwave-Assisted Nanocomposites for Solubility Enhancement of Azelnidipine: Development, Optimization and in vivo Pharmacokinetic Study in Rats - Mankar, Someshwar; Rohom, Ashitosh; Siddheshwar, Suhas (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: The enhancement of drug solubility and bioavailability for orally administered medications remains a significant challenge in pharmaceutical formulations. This study focused on Azelnidipine, a poorly water-soluble drug used to treat hypertension, aiming to improve its solubility and delivery using microwave-assisted nanocomposite technology. Materials and Methods: A 3² factorial design was utilized to optimize the concentrations of polymers HPMC K100M and PVK K-30 in the nanocomposite formulation. The optimization was carried out using Design-Expert® software with a quadratic model validated by ANOVA, ensuring statistical significance. Physical characterization of the polymers, including swelling index and FTIR spectroscopy, was conducted to determine their suitability as carriers. In vitro drug release studies and in vivo pharmacokinetic studies were performed, with in vivo experiments conducted on Wistar rats (n=6 per group) to compare the optimized nanocomposite (AF6) with a marketed product. Results: The optimized nanocomposite displayed a significant improvement in solubility, with the highest solubility observed at 1.685 mg/mL (AF6) and the highest drug content at 91.76% (AF6). In vivo studies demonstrated a peak plasma concentration of 1450.33 ng/mL for AF6, markedly higher than the marketed product's peak of 850 ng/mL. AF6 maintained elevated plasma concentrations over 12 hr and showed a superior AUC of 8608.58 ng/mLh compared to 2818.58 ng/mLh for the marketed product. Conclusion: The study successfully employed microwave-assisted nanocomposite technology to enhance the solubility and bioavailability of Azelnidipine. The optimized nanocomposite Formulation (AF6) significantly outperformed the marketed product in terms of drug content, solubility and pharmacokinetic profile, offering a promising approach to improving oral drug delivery for poorly soluble drugs.
Keywords: Azelnidipine; Solubility enhancement; Microwave-assisted nanocomposites; In vivo; pharmacokinetics; Nanocomposite